Α-Diimine synthesis via titanium-mediated multicomponent diimination of alkynes with C-nitrosos. Issue 5 (18th January 2022) - Frye, Connor W.; Egger, Dominic T.; Kounalis, Errikos; Pearce, Adam J.; Cheng, Yukun; Tonks, Ian A.
Abstract : Alkyne diimination to unsymmetric α-diimines can be achieved via multicomponent reaction of Ti imidos and C -nitrosos. C -nitroso [4 + 2] cycloaddition across a diazatitanacyclohexadiene initiates cascading retrocycloadditions, liberating the α-diimine. Abstract : α-Diimines are commonly used as supporting ligands for a variety of transition metal-catalyzed processes, most notably in α-olefin polymerization. They are also precursors to valuable synthetic targets, such as chiral 1, 2-diamines. Their synthesis is usually performed through acid-catalyzed condensation of amines with α-diketones. Despite the simplicity of this approach, accessing unsymmetrical α-diimines is challenging. Herein, we report the Ti-mediated intermolecular diimination of alkynes to afford a variety of symmetrical and unsymmetrical α-diimines through the reaction of diazatitanacyclohexadiene intermediates with C-nitrosos. These diazatitanacycles can be readily accessed in situ via the multicomponent coupling of TiNR imidos with alkynes and nitriles. The formation of α-diimines is achieved through formal [4 + 2]-cycloaddition of the C-nitroso to the Ti and γ-carbon of the diazatitanacyclohexadiene followed by two subsequent cycloreversion steps to eliminate nitrile and afford the α-diimine and a Ti oxo.